Memory and Violence. Fifty Years After “La Violencia en Colombia” by Bishop Guzman et al - Valencia Gutiérrez, Alberto (Sociedad y Economía, 2012)
This article presents and analyzes the book La Violencia en Colombia. Estudio de un proceso social by Monsignor Germán Guzmán Campos, sociologist Orlando Fals Borda, and jurist Eduardo Umaña Luna. It seeks to explore the conditions upon which this book was written, the sources it uses, the characteristics of its authors, the principal issues it tackles, the sociological approach it suggests, and the way it understands the process, while analyzing what this document means to the process of assimilation and construction of collective memory of the fifties in Colombia.